2016
DOI: 10.1038/srep21609
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of anxiety and depression on the relationship between Attention-deficit/hyperactivity disorder symptoms and smoking/drinking

Abstract: Attention-deficit/hyperactivity disorder (ADHD) has been often found to be comorbid with other disorders, including anxiety, depression, and unhealthy behaviors such as drinking alcohol and smoking. These factors were often discussed separately, and the mediating effects of mental health on substance use are unknown. To study the mediating effects of anxiety and depression on the relationship between ADHD and drinking/smoking behaviors, we conducted a cross-sectional study of 1870 college students from Shangha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
12
1
Order By: Relevance
“…A total score of 46 was used as cutoff point for having childhood ADHD [ 27 ]. The Chinese version of WURS has shown adequate psychometric properties [ 5 , 28 ]. The Cronbach’s alpha was 0.94 in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total score of 46 was used as cutoff point for having childhood ADHD [ 27 ]. The Chinese version of WURS has shown adequate psychometric properties [ 5 , 28 ]. The Cronbach’s alpha was 0.94 in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Recent large-scale epidemiological studies reveal that the prevalence rate of ADHD symptoms among university students varies widely, ranging from 2.8 to 12.3%, and up to 22.8% of the students may demonstrate ADHD sub-threshold symptoms [ 4 7 ]. The chronic condition of ADHD has been consistently shown to be related to impairments across multiple domains of life, such as social relationships, occupational attainment, academic performance, substance use, and other psychiatric comorbidities [ 5 , 8 11 ]. As of yet, however, very few studies have been conducted to examine the prevalence of ADHD symptoms among medical students.…”
Section: Introductionmentioning
confidence: 99%
“…The two first studies were conducted among college students and identified disinhibition, difficulty stopping drinking, lack of premeditation and sensation seeking as significant mediators of the positive association between ADHD (diagnoses, symptoms) and current alcohol use and/or related consequences [27, 31]. The third study was conducted among college students in China [32]. The authors found that anxiety significantly mediated the association between ADHD-HI symptoms and alcohol behaviors (i.e., alcohol use, HED, intoxication), whereas depression mediated both the associations between ADHD-HI and alcohol behaviors, and the one between ADHD-IN and alcohol behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the personality dimension of impulsivity. The trait of hyperactivity-impulsivity has a robust impact on smoking and drinking behaviours, but in one study, this relationship was found to be mediated by anxiety symptoms, and greater anxiety symptoms were associated with an increased risk of smoking and drinking behaviours [39]. This suggests that impulsivity is related to both anxiety symptoms and the propensity to use substances, which implicates it as a factor potentially explaining the linkage between anxiety and SUDs.…”
Section: Etiological Models Explaining the Anxiety And Sud Comorbiditymentioning
confidence: 98%